Limbah hasil produksi budidaya ikan sistem karamba jaring tancap di Desa Eris, Talikuran dan Kaima Kabupaten Minahasa - Asmirawati Zai; Diane J. Kusen; Suzanne L. Undap; Novie P.L. Pangemanan (e-Journal BUDIDAYA PERAIRAN, 2023)
This study aimed to obtain the amount of organic waste, nitrogen and phosphorus that wasted to  lake and measuring water quality parameters, temperature, dissolved oxygen (DO), acidity (pH) and dissolved solids (TDS) in the area of fixed net cages at Lake Tondano in the villages of Eris, Talikuran and Kaima. This research was carried out in Lake Tondano, Eris, Talikuran and Kaima villages . The time of the study was carried out from March to July 2022. This study used     a descriptive exploration method. Data obtained included primary and secondary data. Primary data otained from interview results and parameter measurements of the water quality in the field (in situ). Secondary data obtained through various resources such as journals and the results of previous studies related to the topic under study. The data of organic waste, nitrogen, and phosphorus were analyzed descriptively using Schmittou method. The results of analyzing the parameters quality of water was presented in the form of tables and graphs then compared with the class of water quality standards in Government Regulation Number 22, 2021 regarding the Implementation of Environmental Protection and Management. The results showed that the amount of organic waste in Eris Village was 874.74 tons/year, Talikuran village 170.52 tons/year, and kaima village 105.80 tons/year, the amount of nitrogen waste in Eris village is 49.86 tons/year, Talikuran village 9.67 tons/year, and kaima village 6.00 tons/year, the amount of phosphorus waste in Eris Village is 17.24 tons/year, Talikuran Village 3.35 tons/year and Kaima Village 2.08 tons/year. The temperature in Eris Village is in the range of 27.4-29.5 °C, Talikuran Village is 26.5-30.3 °C and   Kaima Village is 26.6-30 °C, DO in Eris Village is 5.25-6, 74 mg/L, Talikuran Village 3.76-6.69 mg/L and Kaima Village 4.86-7.18 mg/L, pH in Eris Village was in the range of 7.2-7.9, Talikuran Village 7.1-7.8 and Kaima Village 7,3-7,8, TDS in Eris Village is in the range of 0.104-0.114 g/L, Talikuran Village is 0.117-0.160 g/L and Kaima Village is 0.104-0.114 g/L. The measured water quality parameter data still meets the water quality standard value.